Evaluasi User Experience Pada Game PC Building Simulator Dengan Menggunakan Metode Game Experience Questionnaire (GEQ) - Abdur Rahman; Retno Indah Rokhmawati; Hanifah Muslimah Az-zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Vocational High School first in the field of Computer Network Engineering (CNE) e-learning which is often used as a learning medium about assembling a computer or PC. Currently, one that is being used for computer learning through STEAM is the PC Building Simulator game. PC Building Simulator game is an online game for simulating assembling a Personal Computer (PC). The aim of the study is to see whether the UX value is good The Game Experience Questionnaire is an evaluation instrument designed with a game objective in mind. The number of respondents used 30 participants who are students from class 10 majoring TKJ-1 at SMKN 3 Malang who have used e-learning and have knowledge of e-learning. The method used is quantitative data taken using a questionnaire. the results of the UX value evaluation, get a score of 3.07 in either category or agree. Therefore, the PC Building Simulator game media can be used in class 10 TKJ learning, this competency aspect has a good value, which shows that PC Building can still be played by new players who are not familiar with simulator type games. The problems that mostly arise in all assignments are the limitations of the devices or laptops owned by students, the devices used by students are inadequate, the students' difficulties in translating English, the students do not understand the mission in the game. Keywords: vocational, game, GEQ, CNE,UX.